THE GENRE ANALYSIS OF FOOD LABEL FOR SUPPORTING SMALL AND MEDIUM ENTERPRISES TO JOIN INTERNATIONAL TRADES - Sakitri, Wijang; Ariani Wulansari, Nury (Universitas Negeri Semarang, 2014)
Label is necessary for trades and education. In business world, one of the requirements that should be fulfilled by the owner of industries or Small and Medium enterprises to go international is label. In education, how to make label should be taught as the students of economics faculty are encouraged to become enterpreneurs. This study focuses on the analysis of food label genre. It aims to explain how the stages of food label under study are structured, what stages of food label have in common, and how persuasion, and information is realized. Generic analysis based on social function and systemic functional analysis are used for analyzing thirty food labels as data. In selecting the data, random sampling technique was implemented. Thirty two stages were found in the food labels. However, there was not any label under the study that have the same order of stages. The realization of persuasion, product identification and information were word group, word group and numbers, declarative sentences, and imperative sentences.